Chronic Benign CD8+ Proliferation: A Rare Affection that Can Mimic a Lymphoma Relapse - Osovská, Marcela; Janíková, Andrea; Křen, Leoš; Marečková, Andrea (Case reports in hematology, 2019)
Chronic benign CD8+ proliferation is a rare syndrome that can take the form of a variety of other diseases. Peripheral adenopathy, cytopenia, and infiltration of the liver, kidneys, bowels, or other organs are the most common clinical presentations of the syndrome. CD8+ expansion can be clonal and nonclonal. It generally occurs in patients with innate or acquired immunodeficiency (HIV+) or in patients receiving immunosuppressive therapy. It has been found repeatedly in patients who developed severe hypogammaglobulinemia after treatment with rituximab. Diagnosis of the disease can be difficult because it can mimic relapse of a lymphoma, and a common biopsy examination cannot identify the problem at first. The authors describe a case of a patient pretreated with rituximab who developed agammaglobulinemia and peripheral adenopathy. Biopsy of an enlarged lymph node showed "reactive lymphadenitis." Additionally, a flow-cytometric examination revealed a pathological population of CD8+ lymphocytes. The treatment, which differed from treatments of lymphoma relapse, consisted of corticosteroids and IVIG substitutions and has led to a regression of clinical symptoms. With more frequent usage of rituximab, one can expect increased occurrence of a very rare CD8+ expansion that can reliably emulate the relapse of a lymphoma.